Soft tissue mesenchymal tumour – a case report with review of literature. (2017) - Chowdhury, Debkumar; Chudy, Michal; Bhattacharya, Sanjeet
Highlights: Benign mesenchymal tumours are commonly located in the extremities. Incidence of soft tissue sarcoma is 1 in 100 of all soft tissue tumours. Clinical findings including imaging and immunohistochemistry play a vital role in the diagnosis. Multidisciplinary approach is required from the outset to ensure best patient outcome. Abstract: Introduction: Soft tissue mesenchymal tumours are a common occurrence in surgical practice with particular predilection for the extremities. Approximately 1 in 100 soft tissue tumours are found to be sarcomas. The main concern is to exclude any evidence of malignancy. Both imaging studies and a detailed histological analysis is required to ensure that a diagnosis of a high-grade tumour is not missed. Presentation of case: Here we present a 38-year-old previously fit and well gentleman with a slowly growing lump in the upper aspect of his abdomen over the previous year being completely asymptomatic from it. He underwent ultrasound, computed tomography and magnetic resonance imaging of the lump. He underwent ultrasound guided biopsy with eventual wide local excision of the lump for a complete histological assessment. This was noted to be a soft tissue mesenchymal tumour. Discussion: We highlight the importance of review of the literature and the use of markers that enable histopathologist reach an eventual diagnosis. Mesenchymal tissue during development differentiates into fat, skeletal muscle, peripheral nerves, blood vessels and fibrous tissue. Thereby any of these components may give rise to a tumour. In the majority of cases, the patient is asymptomatic unless there is invasion of nerve sheath or the effects of mass effect. Conclusion: Our case is unique due to location of the tumour and its immunohistochemistry findings which required frequent and extensive discussion at our national sarcoma soft tissue meeting. The importance of surgeons working with histopathologists was also highlighted in our case.